Utilization of Healthcare Services and Perceptions of Corruption in Romania - Precupețu, Iuliana; Pop, Cosmina-Elena (Calitatea Vieții, 2020)
In Romania, perceptions of corruption in both general practice (GP) services and hospital/specialized care are very high, situating the country in the third place in the EU. In this paper, we set out to explore the association between socioeconomic status, utilization of healthcare, social exclusion on the one hand, and perception of corruption in healthcare services in Romania, on the other hand. We mainly try to understand if perceptions of corruption are dependent on utilization of healthcare, seen as a proxy for personal experience. We use European Quality of Life Survey, the 2016 wave for Romania, and we carry out descriptive and explanatory linear regression analysis in order to shed light on perceptions of corruption in the Romanian medical system. Results show a slightly different picture between perceptions of corruption in primary services and views of the phenomenon in hospital care. Corruption in GP provisions appears to be an educated guess, depending on higher socioeconomic status. Insights on this type of corruption are not dependent on utilization of healthcare. Perceptions of corruption in hospital services are associated with the level of economic resources and are dependent on personal experience.